Recent advances in food allergy - Alcocer, Marcos Julio Caruso; Ares, Silvia de la Cruz; López-Calleja, Inés (Instituto de Tecnologia de Alimentos, 2016)
Food allergy is a public health issue that has significantly increased worldwide in the past decade, affecting consumers’ quality of life and making increasing demands on health service resources. Despite recent advances in many areas of diagnosis and treatment, our general knowledge of the basic mechanisms of the disease remain limited i.e., not at pace with the exponential number of new cases and the explosion of new technologies. Many important key questions remain: What defines a major allergen? Why do some individuals develop food allergies and others do not? Which are the environmental factors? Could the environmental factors be monitored through epigenetics or modified by changes in the microbiome? Can tolerance to food be induced? Why are some foods more likely to trigger allergies than others? Does the route and timing of exposure have any role on sensitization? These and many other related questions remain unanswered. In this short review some of these topics are addressed in the light of recent advances in the area.